Computational laser micromachining for machining PMMA - Tiong, Chung Shia (2010)
Laser micromachining has many technological advantages compared to conventional technologies, including design flexibility, production of complex shape and possibility of rapid prototyping. Typical problems that may be faced with laser micromachining are laser-induced debris, large heat-affected zone and laser penetration depth. Frequently, high quality components are obtained by chance or at the expense of time and money due to inaccessible machining dimension, improper set of process parameter and large uncertainty in the process itself. To solve these problems, virtual laser micromachining with the aid of computational model is greatly desirable. This thesis presents a computational laser micromachining model for machining Polymethyl Methacrylate (PMMA). Laser micromachining parameters considered were laser power, spatial velocity and spot size. Finite element models were developed to simulate laser micromachining of PMMA. Time-dependent thermal analysis was used as analysis type. The geometry of the computational model is limited to two-dimensional (2-D) model and uniform mesh design is used. Material was modeled as isotropic and properties were obtained from literature. From result, the computational model was validated by comparing computed size of major cutting zone with experimental result. After validation, laser micromachining was simulated for varying laser parameters generated by design of experiment (DOE) in STATISTICA. These results will be analyzed in STATISTICA and the feasible process parameters were identified. Different parameter combinations provide different contour pattern and different size of major cutting zone. Laser power was found to be the most significant effect to the size of major cutting zone, followed by laser spot size and spatial velocity.